Indian climate change policy: Exploring a co-benefits based approach - Dubash KNavroz; Raghunandan D; Sant Girish; Sreenivas Ashok (Economic & Political weekly, 2013)
There is a growing body of climate-related policy in India; at the same time, there is no clear and consistent approach or framework that directs and guides these efforts. In this paper, we propose and develop a methodology for operationalising a co-benefits approach to climate policy formulation. We use the technique of multi-criteria analysis, which requires making choices between and examining trade-offs across multiple objectives of policy, such as growth, inclusion and environment. In addition, we develop a framework for consideration of implementation issues. We focus on policies related to energy; but we believe the approach can also be modified to address adaptation concerns. The structured tool of the sort proposed here would hopefully contribute to more informed and deliberative decision-making on climate-related issues.
Keywords: Climate change policy